MADEI PEMBENTUKAN PSR J1141-6545 - Irfan Hakim, Muhamad
Abstract: WE investigate the candidates of PSR J1141-6545 system. The optical companion is probably a white dwarf which formed prior to the birth of the pulsar. The required mass of primary star to produce a white dwarf should be 6 M® I 8 Mo. It has to transfer sufficiently mass to the secondary (which is initially lighter than the primary, q = M4°)/4i°) 1) in order for the latter to explode in a supernova. Before supernova, the secondary evolve through a common envelope (because q become more than 2.5) producing a helium star. We also discuss the constraint for the initial orbital period, cases of mass transfer, and efficiency factor (i) for common envelope evolution.